Effect of auxins on root development in yam (Dioscorea rotundata) vine - Acha, I.A.; Shiwachi, H.; Asiedu, Robert; Akoroda, M.O. (Wiley, 2004)
Treatment with indolebutyric acid (IBA) significantly increased the number of roots produced by vine cuttings of ten Dioscorea rotundata cultivars. Some cultivars could be propagated by layering, especially with IBA treatment, but layering does not appear to be feasible for use on farms.